2023
DOI: 10.24875/gmm.m19000324
|View full text |Cite
|
Sign up to set email alerts
|

Acquired hemophilia

Abstract: Acquired hemophilia (AH) is an autoimmune hemostatic disorder mediated by autoantibodies directed against factor FVIII:C. In 52 % of cases, the cause is unknown or is not associated with other pathological entities; in the rest, there are concomitant factors: lupus, rheumatoid arthritis, cancer, pregnancy, and medications. In Mexico, there is not a registry of AH, and awareness of the disease among health personnel is low. The groups with the highest incidence are women of childbearing age and individuals olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
3
0
2
Order By: Relevance
“…Studies have shown that endocrine related pregnancy failures are likely to occur early in pregnancy, indicating that hormonal regulation might play crucial roles in attachment and early implantation of an embryo into the uterus [ 26 ]. The maternal hypercoagulable state of blood is a physiological change in the blood system during normal pregnancy [ 27 ], and when excessive hypercoagulability of the blood occurs, the blood develops a pathological condition which predisposes to thrombus formation called prethrombotic state (PTS). Many studies have demonstrated that PTS, either hereditary or acquired, is associated with an increased risk of RPL [ 28 , 29 ].…”
Section: Primary Risk Factors For Rplmentioning
confidence: 99%
“…Studies have shown that endocrine related pregnancy failures are likely to occur early in pregnancy, indicating that hormonal regulation might play crucial roles in attachment and early implantation of an embryo into the uterus [ 26 ]. The maternal hypercoagulable state of blood is a physiological change in the blood system during normal pregnancy [ 27 ], and when excessive hypercoagulability of the blood occurs, the blood develops a pathological condition which predisposes to thrombus formation called prethrombotic state (PTS). Many studies have demonstrated that PTS, either hereditary or acquired, is associated with an increased risk of RPL [ 28 , 29 ].…”
Section: Primary Risk Factors For Rplmentioning
confidence: 99%
“…podrían presentar dicha enfermedad en situaciones especiales como, por ejemplo, en el Síndrome de Turner o en situaciones de consanguinidad (heredando dos cromosomas X mutados, uno del padre hemofílico y el otro de la madre portadora) 1 .…”
Section: Ellasunclassified
“…La hemofilia, en términos generales, es un trastorno de la coagulación de origen genético, con un patrón hereditario recesivo asociado al cromosoma X. Es importante conocer que la tercera parte de las personas hemofílicas no tienen antecedentes familiares de este trastorno, tratándose de una mutación de novo 1 .…”
Section: Introductionunclassified
“…Of those, 72% are covered by the Instituto Mexicano del Seguro Social (IMSS). A further 32% of patients are covered by the Secretar ıa de Salud [52]. The experts (n=7) reported that around 60% of patients with hemophilia in Mexico are treated within IMSS, whereas 23% and 18% are treated within Seguro Popular and Instituto de Seguridad y Servicios Sociales de los Trabajadores del Estado (ISSSTE), respectively.…”
Section: Patient Distributionmentioning
confidence: 99%